The principle of proportionality and strict liability of football clubs for the behavior of spectators at UEFA competitions - I. A. Vasilyev (Правоприменение, 2021)
The subject. This article is devoted to the content of the principle of proportionality in disputes about the strict liability of football clubs for the behavior of spectators. The proportionality means that the sanction corresponds to the offense and it has two dimensions. Firstly, the more serious the offense is the higher the sanction should be. Secondly, proportionality protects sport from unreasonably low sanctions while the violation is serious.The purpose of the study is the content of the principle of proportionality: the use of related principles of sports jurisprudence, exceptional circumstances (mitigating and aggravating) in the practice of applying clubs` strict liability for spectators` behavior in UEFA competitions over the period 2007-2021. Liability without fault increases the value of investigating the factual circumstances of a dispute. The broad discretion of the bodies raises the question of the validity of the choice of aggravating circumstances or the refusal of mitigating circumstances. Therefore, the jurisdictional authority in each specific dispute must search for exceptional circumstances thereby fulfilling the principle of proportionality. The second important nuance of strict liability in the UEFA regulations is the difference in the interconnection between violations and sanctions. In some articles, the sanction is predetermined. It is possible to reduce such a sanction only in the presence of an exceptional circumstance and to increase it in the presence of an aggravating circumstance. Separately considered, in conjunction with the principle of proportionality, other principles: principles of predictability of sanctions, equal treatment, the precedent value of decisions on similar disputes (stare decisis).Methodology. The methodological basis of the stated research involves the generalization and analysis of the practice of two institutions of sports jurisprudence. Firstly, the jurisdictional bodies of UEFA are publicly available, as well as available to the author, but currently not available for free download on the UEFA website. Secondly, the relevant decisions of the Court of Arbitration for Sport are in the public domain. Turning to the approaches of law enforcement officers regarding the content of the principle of proportionality meant comparing positions that did not differ in inconsistency. As a result of the analysis of the practice were systematized and identified typical exceptional circumstances, unique exceptional circumstances, and specific enforcement of the principle of proportionality.The main results of research and the field of their application. The article examined the normative limits of sanctions in the UEFA Disciplinary Regulations; exceptional circumstances affecting the choice of sanction; search by the law enforcement officer of the content of exceptional circumstances; principles of predictability of sanctions, equal treatment, the precedent value of decisions on similar disputes (stare decisis) in connection with the verification of sanctions for proportionality. Compliance with the principle of proportionality, in this case, should protect the club from an unreasonably harsh and grossly disproportional sanction. Therefore, it is important to analyze the factual circumstances: which of them are mitigating and which are aggravating. In other categories of offenses, the sanction remains at the discretion of the jurisdictional authority. In such violations, the principle of proportionality takes on a special value. The more flexibility in the choice of sanction is, the higher is the risk of abuse by the jurisdictional bodes. UEFA`s enforcement practice is seeking exceptional circumstances that are not consistent enough to be predictable. Some consistency exists only concerning aggravating circumstances. There is an unreasonably strict approach to mitigating circumstances. The practice of CAS does not differ from the practice of UEFA in terms of strict liability compositions. The principle of proportionality in sports jurisprudence can be interconnected with other legal concepts. Such concepts are equal treatment, predictability, and so-called stare decisis.Conclusions. For the slightly undisputed observance of the principle of proportionality, several requirements must be fulfilled. First, analyze the factual circumstances to find exceptional circumstances among them. Secondly, always choose the minimum sanction in the absence of aggravating circumstances, since strict liability is a forced legal institution. Thirdly, indicate in the decisions what circumstances are mitigating, what aggravating circumstances have been established, and how they both affect the choice of a sanction. Fourth, use the previous decisions of the UEFA`s jurisdictional bodies and CAS of the strict liability offenses when the actual circumstances are close.